A kind of bilayer structure ceramic scintillators designed for phoswich detectors. Issue 12 (31st July 2017) - Hu, Zewang; Chen, Xiaopu; Ding, Dongzhou; Cao, Maoqing; Shi, Yun; Kou, Huamin; Chen, Haohong; Xie, Tengfei; Wu, Lexiang; Pan, Yubai; Li, Jiang
Abstract: The phoswich detectors can determine the location of nuclear interactions with the matrix and it is an effective approach to improve the spatial resolution at the edge of the field of view in positron emission tomography. In this study, we proposed a kind of bilayer structure garnet ceramic scintillators for phoswich detectors. Bilayer Pr:LuAG/Ce:LuAG ceramic scintillations with different thickness ratio were fabricated through solid‐state reaction and vacuum sintering without further cutting or stacking process. The phase, microstructure, fluorescence, and scintillation properties were characterized and studied. The decay time of the Pr:LuAG layer was about 21.8 ns while that of the Ce:LuAG layer was 58.6 ns. Different 5d‐4f emission bands of 290‐450 and 475‐700 nm were observed in the Pr:LuAG layer and Ce:LuAG layer, respectively. These two features meet the basic requirements of phoswich detectors. Separation of interactions with γ‐ray in different layers has achieved in the pulse height spectra. These properties reveal that this kind of multilayer structure garnet ceramic scintillators have potential application value in the field of phoswich detectors.